Spanish Verbalisations and the Internal Structure of Lexical Predicates - Fábregas, Antonio (Routledge Studies in Hispanic and Lusophone Linguistics, 2023)
Spanish Verbalisations and the Internal Structure of Lexical Predicates provides the first comprehensive and empirically detailed theoretical analysis of the different ways in which Spanish builds verbs from nouns and adjectives. This book poses questions about the nature of theme vowels, parasynthesis and the structural relation between the three major lexical word classes from within a Neo-Constructionist framework that highlights the correlations between the syntactic and semantic behaviour of verbs and their morphological make up. Provided within are detailed empirical descriptions of each of the nine major ways of building lexical verbs in Spanish, as well as an integral analysis of those patterns that shows the significance of the contrast between them and their uses to address some foundational questions in morphological theory. Spanish Verbalisations will be of particular interest to researchers in formal linguistics and Spanish.